2018
DOI: 10.1007/s11948-018-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Students’ Varied Conceptualizations About Socially Responsible Engineering: A Four Year Longitudinal Study

Abstract: Engineers should learn how to act on their responsibility to society during their education. At present, however, it is unknown what students think about the meaning of socially responsible engineering. This paper synthesizes 4 years of longitudinal interviews with engineering students as they progressed through college. The interviews revolved broadly around how students saw the connections between engineering and social responsibility, and what influenced these ideas. Using the Weidman Input-Environment-Outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…These students' undergraduate experiences do not seem to have bridged the divide between personal and professional values, and may have even reinforced the initial conception that these are distinct spheres. Moreover, Rulifson and Bielefeldt (2018; 2019) have found that professional internships, important developmental experiences during later undergraduate education, can further deprioritize social responsibility as a priority. Without efforts to change a student's ranking of priorities and conception of career responsibilities, social responsibility concerns appear to take a backseat, serving as either a very minimal constraint on job choice or an aspiration that students are willing to defer to a later point in time.…”
Section: Resultsmentioning
confidence: 99%
“…These students' undergraduate experiences do not seem to have bridged the divide between personal and professional values, and may have even reinforced the initial conception that these are distinct spheres. Moreover, Rulifson and Bielefeldt (2018; 2019) have found that professional internships, important developmental experiences during later undergraduate education, can further deprioritize social responsibility as a priority. Without efforts to change a student's ranking of priorities and conception of career responsibilities, social responsibility concerns appear to take a backseat, serving as either a very minimal constraint on job choice or an aspiration that students are willing to defer to a later point in time.…”
Section: Resultsmentioning
confidence: 99%
“…Our research therefore provides some quantitative data that women students who persist in engineering do, on average, express higher desires to work for socially responsible companies than do their male counterparts. This sample, of course, excludes women who leave engineering because they do not see connections between engineering and their senses of professional social responsibility [2][3]. This provides one possible explanation for why women engineering students seem to express greater desires for socially responsible careers: many of those who persist have been able to make the connection between social responsibility and engineering, whereas those who were not able to make the connection may have left.…”
Section: Impact Of Gender On Students' Desires To Work For Socially Rmentioning
confidence: 99%
“…Social responsibility is a key touchstone of the engineering profession, yet research shows that engineering students' perceptions of the importance of public welfare actually decrease as they progress through the undergraduate curriculum [1][2]. This has direct implications for the diversity of engineering students and workforces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineering ethics education could include both microethics (relating to individual actions) and macroethics (the collective responsibility of the profession) [9], as well as targeting both cognitive and affective attributes [10]. It has been demonstrated that engineering students and practitioners possess a range of nuanced understandings about the professional social responsibilities of engineers [11][12][13]. The military is also a profession [4].…”
Section: Introductionmentioning
confidence: 99%